1996
DOI: 10.1177/135245859600200502
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic expectations of patients with multiple sclerosis upon initiating interferon beta-lb: Relationship to adherence to treatment

Abstract: This study, conducted in three separate outpatient health care delivery settings, examined the therapeutic expectations of patients with multiple sclerosis (MS) before they initiated interferon beta-1b therapy, the results of current educational procedures to correct unrealistic expectations, and the relationship between post-education expectations and discontinuing therapy. Ninety-nine consecutive patients were seen in a university based outpatient MS clinic, an academic group practice outpatient MS clinic, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
94
1
9

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 8 publications
8
94
1
9
Order By: Relevance
“…8,30 Studies of adherence to MS therapy in clinical practice have shown that patients are more likely to discontinue DMTs within the first 6 months after initiation of treatment. 5,29 This was also observed in our cohort, indicating that regular patient support during this time may be particularly important. The high discontinuation rate in association with short disease duration and low EDSS score in our cohort is of concern and calls for action.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…8,30 Studies of adherence to MS therapy in clinical practice have shown that patients are more likely to discontinue DMTs within the first 6 months after initiation of treatment. 5,29 This was also observed in our cohort, indicating that regular patient support during this time may be particularly important. The high discontinuation rate in association with short disease duration and low EDSS score in our cohort is of concern and calls for action.…”
Section: Discussionsupporting
confidence: 58%
“…3,4 Discontinuation rates as high as 40% for first-line DMTs have been reported in the MS population. [5][6][7][8][9] Adverse effects,…”
mentioning
confidence: 99%
“…3 Additionally, setting realistic expectations regarding MS treatment and adverse events was associated with improved adherence. [21][22][23] Because FLSs and ISRs are linked to treatment discontinuation and low adherence in patients with MS, setting realistic treatment expectations is critical and should be done tions (acetaminophen and/or an NSAID), dose titration, and administration at bedtime. 7,[18][19][20] Consequently, scheduled use of acetaminophen and/or an NSAID and changing the timing of injection were recommended as management strategies for FLSs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaire 1 responses were received between February 26 and May 4, 2014, and questionnaire 2 responses between September 15 and October 22,2014. From the 183 sites that participated in ADVANCE, 84 investigators met the inclusion criteria and were invited to participate.…”
Section: Responder Demographicsmentioning
confidence: 99%
“…However, the supply of INF-b to patients with RRMS in Malaysia is limited due to its high cost and limited public funds, 2 and studies estimate the rate of non-adherence to INF-b treatment to be 9-21% with the peak period of non-adherence being the first 6 months. [3][4][5] It is vital to ensure that patients adhere to the treatment regimen to obtain the best outcomes and minimise wastage. A pharmacist medication therapy adherence program was set up to improve patient adherence to INF-b treatment and to provide education on RRMS and INF-b.…”
mentioning
confidence: 99%